2019
DOI: 10.1021/acsami.9b15860
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Photothermal Patterning of Doped Polymer Films

Abstract: Organic semiconductors (OSCs) offer a new avenue to the next-generation electronics, but the lack of a scalable and inexpensive nanoscale patterning/deposition technique still limits their use in electronic applications. Recently, a new lithographic etching technique has been introduced that uses molecular dopants to reduce semiconducting polymer solubility in solvents and a direct-write laser to remove dopants locally, enabling rapid OSC etching with diffraction limited resolution. Previous publications postu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…By comparison, DISC photopatterning uses polymer “out of the bottle” and can be adapted to pattern both doped and intrinsic polymers. [ 36 ] Several publications have now demonstrated diffraction limited patterning with a variety of form factors. Comparing all of the techniques, only DISC photopatterning and electrohydrodynamic organic nanowire printing [ 22 ] were able to achieve reliable wire/circuit fabrication to the diffraction limit of ≈300 nm using non‐chemically altered OSCs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, DISC photopatterning uses polymer “out of the bottle” and can be adapted to pattern both doped and intrinsic polymers. [ 36 ] Several publications have now demonstrated diffraction limited patterning with a variety of form factors. Comparing all of the techniques, only DISC photopatterning and electrohydrodynamic organic nanowire printing [ 22 ] were able to achieve reliable wire/circuit fabrication to the diffraction limit of ≈300 nm using non‐chemically altered OSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Our fastest recorded dissolution times are ≈1 μs per pixel, which is near the limit of mass transport by a fluid over the appropriate volume. [ 36 ] Figure 2e depicts the geometry of the doping and dedoping steps. Figure 2f shows a schematic of the photopatterning geometry that enables conductivity measurements of a single nanowire.…”
Section: Resultsmentioning
confidence: 99%
“…This conclusion is consistent with recent work by Su et al, who found that at low to moderate light intensities (<10 kW/cm 2 ) dissolution at 405 nm was dominated by photodedoping. 30 However, since the form of the rate law is identical with or without the reaction present, it appears that the resolution of the process is entirely controlled by the thermal dedoping step shown in Figure 1.…”
Section: E X Y Zmentioning
confidence: 99%
“…To minimize electronic device feature sizes, eliminate crosstalk in circuitry, and scale-up soft matter opto-electronic device fabrication, foundry-compatible patterning of all functional layers is essential for creating multiple circuitry layers, and systems integration 1 – 6 . Specifically, high-resolution patterning of robust semiconductor films in thin-film transistor (TFT) arrays must optimize the charge transport and on-current/off-current ratio ( I on : I off ) ratio, while achieving reliable deposition by solution-processing of all additional non-TFT components, including the gate dielectric/gate contact in top-gated TFTs, and the source-drain electrodes in top-contact TFTs, as well as planarization/passivation layers in both architectures 7 12 . Several pioneering studies realized patternable photo­crosslinked polymer semiconductors by appending crosslinkable moieties to the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%